Discovering and empowering rural women's skills based on creativity highlights community potential (creativepreneur) program adapting a sustainable development approach (circular economy: sustainability) in Sungai Petani, Kedah, Malaysia - Md Hashim, Azhari; Md Yusoff, Irwan Syah; Hasan, Asrol; Subri, Shafilla; Mohd Khalis, Faryna (Universiti Teknologi MARA, Kedah, 2024)
This study aims to provide a comprehensive understanding of how to identify and enhance creativity and innovation abilities by utilizing the "waste to wealth" sources within the framework of the circular economy concept. The primary goal is to support the rural women's community in Sungai Petani, Kedah, Malaysia. The main challenge faced by this community is the lack of innovative utilization of available resources, without incurring significant expenses (Do-It- Yourself), to create a marketable product of value. This program aims to identify recycled materials as a means of generating revenue by incorporating elements of "designer touch" through brainstorming and product innovation. The program offered two primary improvements in local products, specifically 'Buah Kulim' and shellfish sources. Consequently, the community receives education indirectly by becoming aware of the increase in home income, while the environment benefits from the development of handcraft items and the local economy, leading to its sustainability. Furthermore, this program is anticipated to emphasize and promote the enhancement and execution of Sustainable Development Goals (SDG).